2019
DOI: 10.1186/s12871-019-0737-3
|View full text |Cite
|
Sign up to set email alerts
|

Intubation of non-difficult airways using video laryngoscope versus direct laryngoscope: a randomized, parallel-group study

Abstract: Background The video laryngoscope is recommended for intubating difficult airways. The present study aimed to determine whether the video laryngoscope can further improve intubation success rates compared with the direct laryngoscope in patients with non-difficult airways. Methods In total, 360 patients scheduled for elective abdominal surgeries were randomly assigned to undergo intubation using either a video laryngoscope ( n = 179) or a dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 24 publications
0
30
1
2
Order By: Relevance
“…Most of the VL studies compared glottis visualization, intubation success rate at overall and/or the first attempt, time to intubation, and complication, with those observed using the Macintosh laryngoscope. In many studies, VL has been reported to improve glottis visualization, increase intubation success rate, reduce intubation attempts, reduce pressure on laryngeal structures, and reduce complications compared to those observed on using the Macintosh laryngoscope [3][4][5][6][7][8][9]16]. Since the VL is evolving rapidly and has various advantages over Macintosh laryngoscope, it is considered that VL will become a routine practice in airway management during anesthesia in place of the Macintosh laryngoscope in the near future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the VL studies compared glottis visualization, intubation success rate at overall and/or the first attempt, time to intubation, and complication, with those observed using the Macintosh laryngoscope. In many studies, VL has been reported to improve glottis visualization, increase intubation success rate, reduce intubation attempts, reduce pressure on laryngeal structures, and reduce complications compared to those observed on using the Macintosh laryngoscope [3][4][5][6][7][8][9]16]. Since the VL is evolving rapidly and has various advantages over Macintosh laryngoscope, it is considered that VL will become a routine practice in airway management during anesthesia in place of the Macintosh laryngoscope in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the method of intubation has changed from that involving a direct glottic view to an indirect glottic view because video laryngoscopes (VL) have several advantages such as improvement of glottis visualization, a higher intubation success rate, reduction in intubation attempts and complications compared to direct laryngoscopes [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…14 Video laryngoscopy has been shown to have higher first-pass success rates and fewer complications. 29 , 30 In addition, direct laryngoscopy generally requires that the proceduralist’s face is closer to the patient’s mouth than is required for video laryngoscopy. For these reasons, we chose to test the barrier shield using the video laryngoscopy technique.…”
Section: Discussionmentioning
confidence: 99%
“…Mogućnost uporabe naprednih pomagala za intubaciju poput videolaringoskopa ili Bonfilsova rigidnog endoskopa iskusnim korisnicima omogućava sigurniju i bržu intubaciju. 7 Pri odabiru lijekova za indukciju anestezije u pacijenata s PDA-om bitno je održati sustavni vaskularni otpor, očuvati funkciju lijevog srca te izbjegavati smanjenje plućnoga vaskularnog otpora. 8 U bolesnika s teškom disfunkcijom lijeve klijetke i smanjenom srčanom rezervom, kod kojih se zbog prevencije neželjenih događaja mora očuvati preostala funkcija miokarda, lijek izbora jest etomidat zbog njegova protektivnog učinka na srčanu frekvenciju, srednji arterijski tlak te sustavni vaskularni otpor.…”
Section: Raspravaunclassified